Breaking the barriers: the construction and deconstruction of language - Rivas Renderos, Gabriela (My University, 2019)
Indigenous peoples have repeatedly mentioned that it is hard for them to make connections to this country because of the language barriers they face, and have been facing, since the colonization period. This is also due to the fact that Indigenous Peoples have to deconstruct the English language in order to be able to understand/process the input they are receiving. This is why it is hard for them to make meaningful connections to Canada; Language for Indigenous peoples is used as a base foundation that they build their society on and around. Communication is used to pass on important information from generation to generation and constructs their religion, culture, and beliefs. It would be of benefit to Indigenous peoples if research focused on how they construct and deconstruct the English language in order to make sense of what others are trying to communicate; what are their techniques or strategies, and how could we help them make this whole constructing/deconstructing process easier on them. This could theoretically be beneficial not only for Indigenous peoples, but for immigrants as well. Interdisciplinary Dialogue Project.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: language; indigenous peoples